2016
DOI: 10.1186/s13293-016-0092-8
|View full text |Cite
|
Sign up to set email alerts
|

Workshop summaries from the 2015 Sex and Gender Medical Education Summit: utilization of sex and gender based medical education resources and creating student competencies

Abstract: BackgroundDespite overwhelming evidence that sex and gender are critical factors in the delivery and practice of medicine, there is no unified sex- and gender-based medicine (SGBM) undergraduate medical education curriculum. Two Workshops within the 2015 Sex and Gender Medical Education Summit: a Roadmap to Curricular Innovation sought to lay the framework for such a curriculum.MethodsAttendees to the Sex and Gender Educational Summit self-selected attendance for one of two Workshops: (A) Utilization of SGBM R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 7 publications
0
4
0
2
Order By: Relevance
“…Moreover, Chin et al [28] and McGregor et al [29] suggested capitalizing on successful experiences of curricular integration and combination (women's health, emergency medicine, and LGBT/LGBTQI health and wellbeing).…”
Section: How To Integrate Gender Medicine Into Medical Curricula: Bar...mentioning
confidence: 99%
“…Moreover, Chin et al [28] and McGregor et al [29] suggested capitalizing on successful experiences of curricular integration and combination (women's health, emergency medicine, and LGBT/LGBTQI health and wellbeing).…”
Section: How To Integrate Gender Medicine Into Medical Curricula: Bar...mentioning
confidence: 99%
“…The development of uniform criteria and standards, as are currently being discussed in the United States (McGregor et al, 2016), would be welcome in Austria. At the same time, thought should be given to the possibilities and means of promoting a comprehensive introduction of Gender Medicine at all medical universities with the goal of ensuring over the long term a health care system that takes into account the medically relevant sex and gender differences for women and men.…”
Section: Resultsmentioning
confidence: 99%
“…Still lacking, however, are uniform standards for teaching and research. Recently, there has been a push in the initiatives to develop such standards and uniform criteria, which was apparent inter alia in 2015 in the United States at the Sex-and Gender-based Medical Education Summit (McGregor et al, 2016). Parallel thereto, efforts in this direction are also being made in Europe: in Germany strategies were drawn up for the integration of Sex and Gender Medicine in medical curricula (Ludwig et al, 2015), and joint European projects are being conducted (EUGIM, EuGenMed, GenderMedWiki).…”
Section: Introductionmentioning
confidence: 99%
“…No estudo das variáveis relacionadas ao processo saúde-doença, sexo e gênero estão interligados, de modo que o espaço físico e os comportamentos sociais influem na fisiologia humana (McGregor et al, 2016). Inúmeros estudos sobre temas como farmacoterapia, doenças cardiovasculares, distúrbios do desenvolvimento e comunicação médico-paciente sugerem que sexo e gênero influenciam em estágios distintos de prevenção, diagnóstico, tratamento e prognóstico (Meulen et al, 2017).…”
Section: Introductionunclassified
“…Resultados de pesquisas conduzidas em homens, aplicadas no atendimento clínico de mulheres, contribuíram para disparidades de gênero na assistência à saúde (McGregor et al, 2016). Este fenômeno denominado andronormatividade, em que o homem serve como parâmetro, desconsidera o fato das diferenças fisiológicas das mulheres com efeitos nas respostas a doenças, como a síndrome coronariana aguda, e a medicamentos, podendo levar a tratamentos ineficazes ou a toxicidade a medicamentos (Lagro-Janssen, 2010).…”
Section: Introductionunclassified